A critical scholar's journey in China: A brief Freirean analysis of insider–outsider tensions. Issue 12 (15th October 2018) - Misiaszek, Greg William
Abstract: As a full-time foreign faculty member in the Chinese Normal university system for the past five years, I analyze the contested terrain of being a critical, Freirean educator/researcher as an insider and outsider of Chinese and Western academic systems and societies overall. This autobiographical analysis is within the contexts of China's academic focus on raising their global higher education rankings, along with self-reflectivity of my own multiple, often-conflicting identities and Western-centric Orientalism, theorized by Edward Said, in my legitimization of academic work. The following themes are analyzed through critical and Freirean frameworks: pursuit for top rankings coinciding and conflicting with scholarship breadth and depth, academic freedom, and politics of education; constructs of "harmony" that grounds teaching and research; and select pedagogical commonalities and differences between the East, the Global South, and the West. The article delves into preconceptions, including my own, on what is "worthy" academics from China, "the East", "the West", and the "Global South" with self-reflectivity of problematizing such terminology that covers such immense diversity in all aspects of contexts, including education which underscores the very problems with rankings, especially global rankings which are often Western-centric. All themes will be analyzed within my own, conflicting insider- ness and outsider- ness .